آليات الحجاج التداولي في شعر محمود الوراق - عبدالله، هناء عابدين احمد (جامعة الأزهر - كلية اللغة العربية بجرجا, 2021)
يهدف هذا البحث إلى الكشف عن آليات الحجاج التداولي في شعر محمود الوراق، فقد اشتهر الشاعر في عصره بأنه شاعر الزهد والحكمة والموعظة، ولكي يتمكن الشاعر من تحقيق أهدافه ومقاصده وإقناع المتلقي برسالته، نجده حريصا على توجيه خطابه للمرسل إليه متضمنا الحجة القوية والدليل الساطع حتى يجعله يذعن ويسلم بالنتيجة التي يريدها. وقد اتخذت الدراسة من التداولية منهجا في الكشف عن آليات الحجاج التداولي التي استخدمها الشاعر، وبناء على ذلك فقد جاءت في مقدمة، وتمهيد، وأربعة مباحث تضمنت: الروابط الحجاجية، والعوامل الحجاجية، والسلم الحجاجي، والأفعال الكلامية، وخاتمة أثبت فيها أهم نتائج البحث.
This research study aims to reveal the Techniques of Pragmatic Argumentation in the poetry of Mahmoud Al-Warraq. The poet was famous during his time as a poet of asceticism, wisdom, and exhortation. And for the poet to achieve his goals and convince the recipient of his message, we find him eager to direct his speech to him including the strong argument and bright evidence so that he tries to persuade him and influence him to achieve the goals he seeks. The study was adopted to reveal the Techniques of the Argumentation that the poet used through the Pragmatic Methodology, and accordingly, the study came in a preface, an introduction, and four investigations that included: Argumentative connectors-Argumentative operators Argumentative scales The speech acts, and a conclusion in which the results of the research is proved.
Keywords: الشعر العربي -- الخطاب التداولي -- النقد الأدبي -- الوراق، محمود بن حسن، ت. حو. 225 هـ